Blending Saccharum bagasse and waste cooking oil for biofuel production via microwave co-torrefaction process - Lin, Yi-Li; Zheng, Nai-Yun; Cheng, Hsin-Jou; Chang, Chao-Chin (Fuel (Guildford), 2024)
•Microwave co-torrefaction (MCT) of Saccharum bagasse has high potential for producing high quality renewable biochar.•The HHV of biochar increased to 16–25 MJ/kg after MCT.•Satisfactory energy efficiency can be suitable for sustainable reuse.•An environmental perspective with 77% less CO2 emissions than burning bituminous coal. An efficient technology for producing renewable energy is urgently being developed due to the limited non-renewable resources, while disposing of biowaste and achieving zero-waste generation. To achieve the goals, this work explored the yielding of biochar as renewable energy by simultaneously recycling Saccharum bagasse (SB) and waste cooking oil (WCO) via microwave co-torrefaction (MCT). Influencing factors, including different torrefaction temperature (200–300 °C), reaction time (10–30 min), and WCO blending ratios (0%–15%), were systematically assessed using the box-behnken design (BBD) method. Results showed that the reaction temperature had a dominant impact on the biochar of higher-heating-value (HHV), followed by the WCO blending ratio. The HHV of the optimal biochar (24.7 MJ/kg), produced through MCT of SB at 300 °C for 26 min and blended with 15% WCO, was only marginally higher by 0.9% than the second highest HHV of the B12 biochar (24.5 MJ/kg), produced through MCT of SB at 300 °C for 20 min and blended with 15% WCO. Therefore, the B12 biochar was selected as the best condition in terms of energy efficiency. The B12 biochar exhibited superior energy density of 1.5, energy yield of 98.0%, fixed carbon content (17.5%), and thermal stability compared with the raw SB. The O/C and H/C ratios of the B12 biofuel were proximate to those of lignite. In contrast to bituminous coal, a 76.7% lower greenhouse gas (GHG) emissions and a satisfactory energy return on investment (EROI = 6.3) were achieved for the B12 biochar. Overall, the MCT of SB and WCO has a high potential in practical application for producing biochar with high HHV and energy density, good thermal stability, superior EROI, and low GHG emissions for providing green and renewable energy.